Trichobezoar Casing Gastric Perforation: A Case Report - Zeeshanuddin Ahmad; Apoorv Sharma; Minhajuddin Ahmed; Vikram Vatti (Iranian Journal of Medical Sciences, 2016)
Trichobezoars are impactions of swallowed hairs in the stomach and occasionally in the intestine. They occur in emotionally disturbed, depressed, or mentally retarded patients who have trichotillomania and trichophagia. Trichobezoars are usually diagnosed on CT scan or upper GI endoscopy. They can give rise to complications like gastroduodenal ulceration, haemorrhage, perforation, peritonitis, or obstruction, with a high rate of mortality. The treatment is endoscopic, laparoscopic, or surgical removal and usually followed by psychiatric opinion. Herein, we report a case of gastric trichobezoar presenting as gastric perforation in a patient of trichotillomania and trichophagia that was accidentally found on laparotomy. As the patient was in shock on admission, relevant history of trichophagia could not be elicited. Henceforth, she was operated for perforation peritonitis. Trichobezoar was discovered intraoperatively and removed. The perforation was repaired with Graham’s omental patch. Postoperatively, history of trichophagia was corroborated with scarring alopecia of scalp. Trichobezoars is usually seen in adolescent girls, often with an underlying psychiatric or social problem. Laparotomy is the gold standard treatment. Surgical treatment should be followed by behavioral and psychiatric treatment. The patient should be vigilantly monitored for this impulsive disorder, as recurrences are common.